2018
DOI: 10.1039/c7tb03251j
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and nano-structured 3D printed titanium implants with a hydroxyapatite coating for improved osseointegration

Abstract: 3D printing technology combined with electrochemical nano-structuring and HA modification is a promising approach for the fabrication of Ti implants with improved osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 52 publications
3
53
0
Order By: Relevance
“…[ 25,39 ] However, nanotube layers on the underlying AM surface did not display any cracks and was in line with the previous study on AM titanium constructs. [ 21,22,38 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 25,39 ] However, nanotube layers on the underlying AM surface did not display any cracks and was in line with the previous study on AM titanium constructs. [ 21,22,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 65 ] Ideally, an optimal titanium implant surface would promote the osteogenic differentiation of host osteoprogenitor cells and then direct bone apposition, as opposed to fibroblastic cell morphology and resultant fibrous tissue encapsulation. [ 21,62,67 ] Cell proliferation and differentiation processes are expected to be an inverse relationship, that is, great differentiation usually coincides with reduced/arrested proliferation. [ 62 ] This is in line with our proliferation and differentiation results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were in‐line with our study that EDS analysis indicated higher amounts of Ca and P deposition on 3D printed anodized Ti6Al4V meshes compared with their non‐anodized counterparts. Qin et al printed square strips using Ti6Al4V powders and formed nanotubular features on these surfaces. Their results indicated enhanced in vitro osteocyte maturation compared with the non‐anodized surfaces.…”
Section: Resultsmentioning
confidence: 99%